Martín Doello Jurado and the teaching of paleontology in the university of Buenos Aires - Aguirre-Urreta, B. (2011)
Doello Jurado was, together with Florentino and Carlos Ameghino, Eduardo l. Holmberg and Ángel Gallardo, part of the last generation of naturalists that characterized the natural sciences in Argentina, mainly in the late 19th century. since young, he was interested in the history of the development of the natural sciences in our country. Ángel Gallardo, his master, designed him traveler naturalist of the national museum of natural History and in this way he started his studies on the marine invertebrates of our continental platform. Afterwards he was Director of the national museum of natural History, at that time in Perú 208 and in two years' time started the construction of the new building, presently in parque Centenario. He was professor of paleontology in the Faculty of exact and natural sciences of the university of Buenos Aires, and he incremented the collections travelling to different regions of the country. He bought several collections of fossils to the famous Krantz geological warehouse of Bonn and to the Geological Institutes of Bonn, Munich and Brunswick and provided plaster casts of Cenozoic fossil mammals from the Buenos Aires natural History museum. Doello Jurado was co-founder of the Argentine society of natural sciences, the Del Plata ornithological society and the journals Physis and El Hornero. He was also member of the national Academy of exact and natural sciences of Buenos Aires and the national Academy of sciences in Córdoba.